Biopsychosocial Spiritual Support from Healthcare Professionals for Mothers Whose Babies in The Neonatal Intensif Care Unit: A Rapid Review - Heni Angraini; Cesa Septiana Pratiwi; M. Hakimi; Herlin Fitriani Kurniawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Most of the deaths in Indonesia occur during the neonatal period. Based on studies, babies who are treated at the NICU require more attention from healthcare professionals and parents. Nursing the baby in the NICU has a negative psychological impact on the mother which can be stressful for the mother. Biopsychosocial Spiritual support is believed to solve this problem. This study aims to review how the healthcare professionals biopsychosocial spiritual support for mothers who have babies in NICU. A rapid review method was performed using a framework consisting of predetermined step. The instrument chosen to assess the quality of the articles was the Joana Brigs checklist from the Joana Brigs Institute. The results of the review found data related to the impact on mothers who had babies in the NICU, coping methods, and forms of support. Studies have also succeeded in exploring the associated hospital programs for managing stress and family anxiety in the NICU. It was also found that concerning how to overcome it, the need for support is actually very necessary for mothers and their families.  Abstrak: Sebagian besar kematian di Indonesia terjadi pada masa neonatus. Berdasarkan studi bayi yang dirawat di NICU membutuhkan perhatian lebih dari tenaga kesehatan maupun orang tua. Perawatan bayi di NICU berdampak buruk pada psikologis ibu yang dapat membuat ibu stres. Dukungan biopsikososial spiritual diyakini dapat membantu permasalahan tersebut. Tinjauan ini bertujuan untuk mereview bagaimana dukungan biopsikosial tenaga kesehatan pada ibu yang memiliki bayi di NICU. Metode rapid review ini menggunakan framework yang terdiri dari langkah-langkah yang telah ditetapkan. Instrumen yang dipilih untuk menilai kualitas artikel adalah cheklist Joana Brigs dari Joana Brigs Institute.  Hasil review ditemukan data terkait dampak pada ibu yang memiliki bayi di NICU, cara mengatasi, dan bentuk dukungan. Ditemukan juga terkait cara mengatasinya, kebutuhan dukungan yang sebenarnya sangat diperlukan bagi ibu dan keluarga.